Potensi Penggunaan Abu Terbang Cangkang Sawit sebagai Adsorben Logam Arsen dari Air Limbah Tambang - Rainiyati Rainiyati; Ahmad Riduan; Sarah Fiebrina Heraningsih (Universitas Batanghari, 2020)
Arsenic is a dangerous compound that accumulates in nature as a result of anthropogenic activities, one of which is gold mining. Effluent originating from the remaining mining is simply abandoned even though it contains Arsenic which is above the threshold set by the Government of the Republic of Indonesia. The purpose of this study was to analyze the ability of palm shell fly ash to remove arsenic in the residual gold mining effluent. The technology applied in this study was absorption by direct mixing followed by settling and filtering. The maximum arsenic removal efficiency achieved in this study was valued at 81.98%. The longer the contact time between the palm shell fly ash and the waste sample, the less the amount of Arsenic in the waste water will be. The results of this study indicate that the method of removing arsenic from wastewater using palm shell fly ash is very effective, easy to apply and cheap in terms of the cost required.